Development of the database for intelligent ship management system. Issue 4 (March 2020) - Li, Guiqin; Li, Yang; Lan, Jian; Zhu, Qiuyu; Lu, Hao; Mitrouchev, Peter
Abstract: In order to provide a data management solution with higher performance, more flexible expansion and more convenient management, the overall scheme of intelligent ship database cluster is studied by the structure of MySQL database management system and MYCAT distributed database middleware. According to the specific requirements of a shipyard for data collection and use, this paper proposes the alarm point information base and alarm point coding mode from the perspective of practicability and convenient maintenance. Shipyard usage feedback indicates that the database is implemented for ship-wide data sharing.